2019
DOI: 10.1002/cncr.32002
|View full text |Cite
|
Sign up to set email alerts
|

“You probably can’t feel as safe as normal women”: Hispanic women’s reactions to breast density notification

Abstract: Background Patient advocacy has led to state‐level legislative mandates for the release of personal mammographic breast density information to women undergoing screening mammography. More research is needed to understand the impact of this information on women’s perceptions and mammography screening behavior. Methods Semistructured interviews were conducted in English and Spanish with 24 self‐identified Hispanic women who had undergone at least 1 mammogram since breast density notification was enacted in New Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 26 publications
1
42
1
Order By: Relevance
“…Although radiologists believe that patient knowledge has increased because of density notification laws, empirical studies with patients paint a more complex picture. For example, qualitative work has revealed poor understanding and negative emotional responses to breast density notification, particularly among women who identify as Hispanic or receive care in safety net settings . Additional research is needed to clarify observed patterns, particularly in light of the rapidly changing policy landscape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although radiologists believe that patient knowledge has increased because of density notification laws, empirical studies with patients paint a more complex picture. For example, qualitative work has revealed poor understanding and negative emotional responses to breast density notification, particularly among women who identify as Hispanic or receive care in safety net settings . Additional research is needed to clarify observed patterns, particularly in light of the rapidly changing policy landscape.…”
Section: Introductionmentioning
confidence: 99%
“…For example, qualitative work has revealed poor understanding and negative emotional responses to breast density notification, particularly among women who identify as Hispanic or receive care in safety net settings. 17,19 Additional research is needed to clarify Cancer April 15, 2020 observed patterns, particularly in light of the rapidly changing policy landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Our brochure could be used in combination with other tools to support women receiving mandatory dense breast notification and improve patient understanding. Future work should focus on development of similar materials in other languages [ 24 , 25 ], and assess their impact on patient psychosocial and behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of providing women with notification about their MBD and its impact on breast cancer risk without accompanying education may have unintended consequences, particularly among Latinas with lower health literacy and limited resources. Two recent qualitative studies with Hispanic women found that MBD notification language was confusing and led to misinterpretation, including misunderstanding of key concepts like masking and breast cancer risk [9, 10]. While MBD notification language elicited worry and anxiety among some women, the majority in one of the studies reported a desire for MBD notification and potential for it to influence future screening, including pursuit of supplemental screening modalities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent qualitative studies with Hispanic women found that MBD notification language was confusing and led to misinterpretation, including misunderstanding of key concepts like masking and breast cancer risk [9, 10]. While MBD notification language elicited worry and anxiety among some women, the majority in one of the studies reported a desire for MBD notification and potential for it to influence future screening, including pursuit of supplemental screening modalities [10]. The likelihood of disparities emerging between women who can pursue supplemental breast screening and women who are less able to do so is also an important consideration [11].…”
Section: Introductionmentioning
confidence: 99%